Immune Activation, Proinflammatory Cytokines, and Conventional Risks for Cardiovascular Disease in HIV Patients: A Case-Control Study in Bahia, Brazil - Brites-Alves, Clara; Luz, Estela; Netto, Eduardo M.; Ferreira, Thalis; Diaz, Ricardo Sohbie; Pedroso, Celia; Page, Kimberly; Brites, Carlos (Frontiers in Immunology, 2018)
Background –Cardiovascular events (CVE), are an increasing cause of morbi-mortality for HIV patients. The antiretroviral therapy (ART), persistent immune activation (PIA), and life style are factors that can increase CVE for such patients. We performed a case-control study to evaluate the role of coinfections and immune markers associated with CVE. Methods – we included patients under ART, with undetectable plasma viral load ≥ 12 months. Patients presenting any condition of risk for CVE were considered cases, and those without CVE risk conditions were controls. History of viral infections (EBV, HCV, HBV, CMV), exposure to antiretroviral drugs, time since HIV diagnosis/under ART, and life style (demographics, weight, smoking, alcohol, illicit drug use) were assessed. CD4/CD8 nadir and current counts, nadir and current CD4/CD8 ratio, immune activation markers (CD4CD38HLADR, CD8CD38HLADR) and serum levels of eight cytokines (IL-2, IL-4, IL-6, IL-10, TNF-alpha, Gama-IFN, MIP-1 alpha, and IP-10) were measured. Results – Two-thirds of patients were males. Cases (N=106) were older (52.8 vs 49.5 years, p=0.002), had higher levels of creatinine (0.97 vs 0.87 mg/dL, p=0.002), and IL-6 (0.67 vs 0.52 pg/mL, p=0.04) than controls (N=114). There was no difference between groups regarding frequency of CD4CD39HLADR+ or CD8CD38HLADR+ cells. We found a significant correlation (all patients) between increased frequency of CD4CD38HLADR+ cells and levels of IP-10 (r= 0.171, p=0.02) and TNF-alpha (r= 0.187, p=0.01). Levels of IL-6 (r= 0.235, p=0.02), TNF-alpha (r=0.267, p=0.01), and IP-10 (r=0.205, p=0.04) were correlated to CD4CD38HLADR+ cells, in controls. Higher frequency of CD4CD38HLADR+ cells was also correlated with levels of IP-10 (r=0.271, p=0.04) in patients presenting with arterial hypertension. Frequency of CD4CD38HLADR+ cells was negatively correlated to levels of IL-2 (r=-0.639, p=0.01) and IL-6 (r=-.0561, p=0.03) in patients with hypercholesterolemia. No association was detected between viral infections or smoking/ alcohol use and immune activation markers. Conclusions: Our results indicate IL-6 levels are associated with increased CV risk. Activated CD4+ T cells were associated with increased levels of pro-inflammatory cytokines.